What is the difference in the destination image of the Russian settlement of Barentsburg on Svalbard archipelago by tourists before they arrive and after they visited it? Recommendations to make Barentsburg more tourist friendly - Galaburda, Marina (UiT The Arctic University of Norway, 2016)
This thesis explores the difference in destination image before and after tourists arrive at the Russian settlement, Barentsburg, in the Norwegian archipelago of Svalbard. Different tourists, who had visited Barentsburg, were the focus of the project. The main concept used throughout this thesis is tourists’ images of the destination. The research that informed this paper also investigated aspects related to the current conditions, opportunities and constraints for the development of tourist activities in this settlement’s territory. The second goal of my research was to disclose potential opportunities, strengths and weaknesses in order to offer recommendations for tourism development at the destination.